Length = 13 = (x + 3)
Width = 14 = (x + 4)
x2 + 7x + 12 = area of the rectangle
can be factored into
(x + 3)(x + 4)
Let L = one of the factors (x + 3)
Let W = the other factor (x + 4)
If x = 10 then
(10 + 3) = 13 = L
(10 + 4) = 14 = W
Checking this can be checked a couple of ways
Plug x = 10 into the original equation
x2 + 7x + 12
102 + 7(10) 12 = 100 + 70 + 12 = 182 = Area
Multiplty the factors
L x W = 13 x 14 = 182 = Area
I hope you find this useful if you have any questions please send me a message.
Answer:
The given point A (6,13) lies on the equation. True
The given point B(21,33) lies on the equation. True
The given point C (99, 137) lies on the equation. True
Step-by-step explanation:
Here, the given equation is : ![y =\frac{4}{3} x + 5](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20x%20%2B%205)
Now,check the given equation for the given points.
1) A (6,13)
Substitute x = 6 in the given equation![y =\frac{4}{3} x + 5](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20x%20%2B%205)
![y =\frac{4}{3} (6) + 5 = 4(2) + 5 = 8 + 5 = 13](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20%286%29%20%2B%205%20%20%3D%204%282%29%20%2B%205%20%20%3D%208%20%2B%205%20%3D%20%2013)
⇒ y= 13
Hence, the given point A (6,13) lies on the equation.
2) B (21,33)
Substitute x = 21 in the given equation![y =\frac{4}{3} x + 5](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20x%20%2B%205)
![y =\frac{4}{3} (21) + 5 = 4(7) + 5 = 28 + 5 = 33](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20%2821%29%20%2B%205%20%20%3D%204%287%29%20%2B%205%20%20%3D%2028%20%2B%205%20%3D%20%2033)
⇒ y = 33
Hence, the given point B(21,33) lies on the equation.
3) C (99, 137)
Substitute x = 99 in the given equation![y =\frac{4}{3} x + 5](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20x%20%2B%205)
![y =\frac{4}{3} (99) + 5 = 4(33) + 5 = 132 + 5 = 137](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B4%7D%7B3%7D%20%2899%29%20%2B%205%20%20%3D%204%2833%29%20%2B%205%20%20%3D%20132%20%2B%205%20%3D%20%20137)
⇒ y = 137
Hence, the given point C (99, 137) lies on the equation.
Answer:
-16 (t+3) (t-3)
Step-by-step explanation:
Answer:
3
Step-by-step explanation:
3+3_3=3
after that 3+2+6+7+7+8+8+9+9+9+9+9+0+0+8+6+5+4+ 5=?
u will do the answer and it will be done
Answer:
Choice 3 is your answer
Step-by-step explanation:
The format of the function when you move it side to side or up and down is
f(x) = (x - h) + k,
where h is the side to side movement and k is up or down. The k is easy, since it will be positive if we move the function up and negative if we move the function down from its original position.
The h is a little more difficult, but just remember the standard form of the side to side movement is always (x - h). If our function has moved 3 units to the left, we fit that movement into our standard form as (x - (-3)), which of course is the same as (x + 3). Our function has moved up 5 units, so the final translation is
g(x) = f(x + 3) + 5, choice 3 from the top.